Inference of molecular divertor density from filtered camera analysis of molecularly induced Balmer line emission during detachment in JET L-mode plasmas. (1st January 2022) - Karhunen, J.; Holm, A.; Lomanowski, B.; Solokha, V.; Aleiferis, S.; Carvalho, P.; Groth, M.; Lawson, K.D.; Meigs, A.G.; Shaw, A.; ,
Abstract: A previously presented Monte Carlo method for estimating local plasma conditions in 2D based on intensity ratios of deuterium Balmer D α, D γ and D ɛ lines was amended to consider also the D α and D γ emission contributions arising from molecular processes. The obtained estimates were used to infer the molecular divertor density with the help of the molecular databases of EIRENE. The method was benchmarked against EDGE2D-EIRENE simulations and observed to reproduce the molecularly induced emission fractions and the molecular divertor densities primarily within 25% of the references. Experimental analysis of a JET L-mode density scan suggested molecularly induced D α and D γ contributions of up to 60–70% and 20%, respectively, during the process of detachment. The independent estimates of the molecular divertor density inferred from the obtained molecularly induced D α and D γ intensities agree within uncertainties with each other. Both estimates show the molecular density increasing up to approximately 1.0–2.0 × 10 20 m −3 at the outer strike point in deep detachment with its ratio to the local electron density agreeing with EDGE2D-EIRENE predictions within the scatter of the experimental data.